Genetic variability among the wild boars (Sus scrofa scrofa), crossbred animals and pigs using microsatellite markers (STRs) - Silva, Paula Viana Correa da [UNESP]; Lui, Jeffrey Frederico [UNESP]; Band, Guilherme de Oliveira [UNESP]; Regitano, Luciana Correia de Almeida; Grossi, Selma de Fátima; Sollero, Bruna Pena; Nunes, Cleujosí da Silva (Brazilian Archives of Biology and Technology, 2011)
The aim of this work was to study the genetic variability among the wild boars, crossbred animals and pigs using microsatellite markers. Five genetic groups were studied. The fragments of three microsatellites developed for Sus scrofa domestica - IGF1, ACTG2 and TNFB - were amplified through PCR technique to evaluate the expected intra populacion variability (He) and observed (Ho) heterozygosity, and endogamy coefficient (F IS ) within each population and inter population variability F IS , testing relationship among five genetic groups to establish the genetic distance among them. The high level of observed heterozygosity values varied between 0.537 and 0.7871. Generally, F IS was low, suggesting that the endogamy did not exist between the tested animals.
Keywords: Molecular genetics; wild boars; Microsatellites; fragments; amplification